Comparison of Vitamin D and Zinc Levels in Women With Diminished Ovarian Reserve Compared to Normal condition: A Case-control Study - Shahintaj Aramesh; Fatemeh Azaraksh; Ramin Jannesar; Marcello Iriti; Fatemeh Bazarganipour (Journal of Holistic Nursing and Midwifery)
Introduction: To date, limited studies have evaluated the relationship between serum levels of vitamin D, zinc and ovarian reserve, which have presented contradictory results. Objective: This study aims to compare vitamin D and zinc dietary intake and serum levels in Iranian women with diminished ovarian reserve (DOR) compared to normal peers. Materials and Methods: The case-control study was performed on 99 women referred to an infertility treatment clinic in Yasuj, Iran, who were selected by a convenience sampling method. The case group (n=55) included women with DOR (anti-Müllerian hormone (AMH) <1 ng/mL and antral follicle count (AFC) <10 in sonography at 3-10 days of menstrual cycle). The control group (n=44) was women with normal ovarian reserve markers. Dietary intake was assessed using the food frequency questionnaire, and the serum concentration of zinc and vitamin D were determined for each participant. The obtained data were analyzed using t-test or chi-square test. The body mass index (BMI) and age were adjusted by the analysis of covariance. Significance level was set at P≤0.05. Results: The mean age of the participants was 33.4±26.58 and 32.4±31.16 years in the case and control groups, respectively. The mean BMI of participants was 27.15±3.97 and 26.35±4.23 kg/m2 in the case and control groups, respectively. After adjusting for BMI and age, dietary intake of vitamin D (6.98±0.57 vs 4.02±1.09; P=0.05; adjusted effect size=0.86) and serum vitamin D level (20.91±5.23 vs 17.12±8.73; P=0.05; adjusted effect size=0.52) levels were significantly higher in the control group compared to the case group. Dietary intake of zinc (8.75±2.55 vs 10.68±4.75) and serum zinc level (87.09±10.02 vs 87.09±10.02) were not significantly different in the control group compared to the case group, after adjusting for BMI and age. Conclusion: Our results on DOR revealed the possible favorable relationship of vitamin D intake and serum vitamin D level with ovarian reserve performance, and this relationship is independent of age and BMI. Further studies, particularly clinical trials, are recommended to clarify the potential positive effects of vitamin D on ovarian reserve in DOR women.